Quality of Life and Functioning of People With Mental Disorders Who Underwent Deinstitutionalization Using Assisted Living Facilities: A Cross-Sectional Study - Mayer, Rejane Coan Ferretti; Alves, Maíra Ramos; Yamauti, Sueli Miyuki; Silva, Marcus Tolentino; Lopes, Luciane Cruz (Frontiers in Psychology, 2021)
Context: People with mental disorders can acquire long-term disabilities, which could impair their functioning and quality of life (QoL), requiring permanent care and social support. Systematic data on QoL and functioning, which could support a better management of these people, were not available. Objective: To analyze the QoL, level of functioning and their association with sociodemographic and clinical factors of people with mental disorders who underwent deinstitutionalization using assisted living facilities. Methods: A Cross-sectional study was conducted between July 2018 and July 2019, through interviews using the World Health Organization Quality of Life (WHOQOL-BREF) to determine the QoL scores, and the World Health Organization Disability Assessment Schedule (WHODAS 2.0) to determine the level of functioning. All adults (≥18 years old) with mental disorders, who underwent deinstitutionalization, users of assisted living facilities and assisted by the Psychosocial Assistance Centers III, in a city in the state of São Paulo, Brazil, were selected. For statistical analysis of the associated factors, Student’s t-test was used for dichotomous variables and ANOVA for polynomial variables. Pearson correlation coefficient was used to measure the association between QoL and functioning scores. Results: Out of 359 people who underwent deinstitutionalization with mental disorders, 147 met the eligibility criteria. The mean total score for the WHOQOL-BREF was 66.5 ± 13.4 and the mean score for WHODAS 2.0 was 10.4 ± 7.6. An association was found between people who were studying (n = 65.8; 95%CI, 63.5–68.1 versus n = 73.9; 95%CI, 67.5–80.3; p = 0.04) and better WHOQOL-BREF QoL scores or WHODAS 2.0 levels of functioning (n = 10.9; 95%CI, 9.6–12.2 versus n = 5.1; 95%CI, 2.5–7.7; p = 0.01). A weak negative correlation (r = 0.41) emerged between higher QoL scores and functioning improvement. Conclusion: This study indicates that the QoL of the sample is associated by their functioning levels, which, in turn, may reflect on their social interactions. Public policies that favor interventions increasing socialization of this population can result in better health outcomes. The QoL and functioning scores provide valuable insights to develop public policies more suited to this population profile.